2015
DOI: 10.1088/0957-4484/26/29/291001
|View full text |Cite
|
Sign up to set email alerts
|

Current rectification in a single molecule diode: the role of electrode coupling

Abstract: We demonstrate large rectification ratios (> 100) in single-molecule junctions based on a metal-oxide cluster (polyoxometalate), using a scanning tunneling microscope (STM) both at ambient conditions and at low temperature. These rectification ratios are the largest ever observed in a single-molecule junction, and in addition these junctions sustain current densities larger than 10(5) A cm(-2). By following the variation of the I-V characteristics with tip-molecule separation we demonstrate unambiguously that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 25 publications
1
50
0
Order By: Relevance
“…The results [21] confirm that all transitions between different spin states of GdW 30 are in good speaking terms with these circuits. Besides, its molecular character ensures that they can be taken out of the crystal and placed individually on a surface or in a device [28].…”
Section: The Resulting Coordination Around Gdmentioning
confidence: 99%
“…The results [21] confirm that all transitions between different spin states of GdW 30 are in good speaking terms with these circuits. Besides, its molecular character ensures that they can be taken out of the crystal and placed individually on a surface or in a device [28].…”
Section: The Resulting Coordination Around Gdmentioning
confidence: 99%
“…Rectification has been studied in a variety of junction setups since the early days of molecular electronics 50,51 . Recent experiments and supporting computational investigations have demonstrated that one can achieve robust molecular diodes with rectification ratios of two and even three orders of magnitude in SAMs 52 and single molecules 53,54 . The mechanism of rectification in many proposed molecular structures is based on the assumption of coherent tunneling, more precisely, on the fact that deep-tunneling conductance is orders of magnitude smaller than resonant transmission, see for example 55,56 .…”
Section: Introductionmentioning
confidence: 94%
“…The commonly examined "tunneling diode" relies on the dramatic contrast between deep tunneling conductance and ballistic transport, see for example recent experiments 52,54 and theoretical studies 55,56 . In these systems, rectification arises e.g.…”
Section: Environmentally Induced Diodesmentioning
confidence: 99%
“…17 Among polyoxometalates, a most promising family would be the single ion magnets and molecular spin qubits LnW30 18,19 and in particular TbW30 which has experimentally be proven to function as a single-molecule rectifier. 20 We chose not to start our theoretical study with these promising families purely because of reasons of computational cost: Lanthanoid complexes need an explicit consideration of the spin-orbit coupling with relativistic pseudopotentials that would make the initial exploration much more challenging. In addition, except for some organometallic 'sandwiches', all the lanthanoid single ion magnets present a larger number of atoms per molecule compared with other simpler families.…”
Section: : Detailed Comments On the Selection Of Molecules For The Ementioning
confidence: 99%